PENGARUH METODE PEMBAYARAN CASH ON DELIVERY PADA APLIKASI SHOPEE TERHADAP DAYA BELI KONSUMEN : Studi Kasus Pada Mahasiswa UINSU - Hsb, Mhd Fathur Rizqi Zuhada; Surbakti, Zein Zahara Br; Khairani, Ema; Silalahi, Purnama Ramadani (Bussman Journal : Indonesian Journal of Business and Management, 2023)
COD is a payment method that is made directly on the spot after the order from the courier is received by the buyer. The method used in this research is a quantitative method in the form of a survey. Data analysis techniques were carried out by utilizing descriptive statistics, using a percentage formula. The results of this study indicate that the Cash On Delivery (COD) payment method affects consumer purchasing power